2018
DOI: 10.5334/tohm.407
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Harmaline Tremor by Activation of an Extrasynaptic GABA<sub>A</sub> Receptor: Implications for Essential Tremor

Abstract: Background: Metabolic imaging has revealed excessive cerebellar activity in essential tremor patients. Golgi cells control cerebellar activity by releasing gammaaminobutyric acid (GABA) onto synaptic and extrasynaptic receptors on cerebellar granule cells. We postulated that the extrasynaptic GABA A receptor-specific agonist THIP (gaboxadol; 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol) would suppress tremor in the harmaline model of essential tremor and, since cerebellar extrasynaptic receptors contain a6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…For example, recent work suggested that α6βδ‐selective agonists might be useful in the clinic as antitremor medications (Handforth et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, recent work suggested that α6βδ‐selective agonists might be useful in the clinic as antitremor medications (Handforth et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…3, B & C) suggests that the α6GABAARs in the cerebellum are the site of action of Compound 6. A previous study indicated that gaboxadol, a selective agonist of the δ-subunit containing GABAARs (δGABAARs), including the α6βδ subtype of GABAARs, significantly suppressed harmaline-induced tremor in wild type, but not in Gabra6 -/or Gabrd -/mice (Handforth et al, 2018), suggesting that the α6βδGABAAR subtype is involved in harmaline-induced tremor. Our previous electrophysiological study on oocyte expressing various recombinant GABAAR subtypes demonstrated that Compound 6 exerted its PAM activity at both α6βγ2 and α6βδ containing α6GABAARs although having a lower efficacy for the α6βδ subtype (Chiou et al, 2018).…”
Section: Cerebellar α6gabaars Are the Site Of Action Of Anti-tremor Effects Of α6gaba A R-selective Pq Compoundsmentioning
confidence: 99%
“…This tremor-burrowing measurement alternation was repeated for several cycles as indicated in each experiment. As harmaline-induced tremor is an action tremor, alternations were designed to refresh the alertness of the mouse once back in the tremor chamber, enhancing tremor consistency by replacing the rest period described in previous studies (Handforth et al, 2018;Martin et al, 2005) with the burrowing activity measurement.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…There is debate over whether phasic inhibition via synaptic GABA-A receptors (activated by benzodiazepines) or tonic inhibition via extrasynaptic GABA-A receptors (predominantly activated by alcohol) is the critical pathogenic mechanism in ET [100]. Recent animal studies have shown that gaboxadol, a highly selective agonist of extrasynaptic GABA-A receptors, is effective at suppressing tremor in a harmaline-induced murine model of ET [101]. A phase 2 trial of allopregnanolone, a progesterone metabolite, which activates both synaptic and extrasynaptic GABA-A receptors is currently underway (Clinicaltrials.gov: NCT02277106).…”
Section: Animal Models and Theoretical Frameworkmentioning
confidence: 99%